2016
DOI: 10.3233/wor-162429
|View full text |Cite
|
Sign up to set email alerts
|

The response of the body when carrying a handbag

Abstract: Continuously carrying a handbag greater than 10% BW can cause musculoskeletal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Simon and Chow [39] using a multi-objective goal programming model recommended that the most critical backpack load should be 13 % of body weight for healthy male college students. Phonpichit et al [40] conducted a study on the body's response to carrying a hand bag and concluded that carrying a handbag greater than 10 % BW continuously can cause musculoskeletal problems. However, there are some limitations on the results obtained from this study.…”
Section: Resultsmentioning
confidence: 99%
“…Simon and Chow [39] using a multi-objective goal programming model recommended that the most critical backpack load should be 13 % of body weight for healthy male college students. Phonpichit et al [40] conducted a study on the body's response to carrying a hand bag and concluded that carrying a handbag greater than 10 % BW continuously can cause musculoskeletal problems. However, there are some limitations on the results obtained from this study.…”
Section: Resultsmentioning
confidence: 99%
“…12 The previous studies also have investigated the effect of type or weight of bags on posture or muscle activity. [12][13][14][15] According to Al-Khabbataz et al 16 , the activity of the rectus abdominis muscle significantly increased with an increase in backpack weight, in that a backpack weight of 20% body weight caused the most significant muscular and postural changes and should be avoided. Phonpichit et al 15 found that the activity of the upper trapezius and erector spinae muscles becomes asymmetrical with increments in handbag weight.…”
Section: Introductionmentioning
confidence: 99%